2019
DOI: 10.2147/jmdh.s216842
|View full text |Cite
|
Sign up to set email alerts
|

<p>Self-Care Adherence And Barriers To Good Glycaemic Control In Nepalese Type 2 Diabetes Mellitus Patients: A Hospital-Based Cross-Sectional Study</p>

Abstract: PurposeThe patient believes in adherence to medication rather than to self-care adherence and lifestyle changes for the management of diabetes. This study was carried out to establish the association of self-care adherence and their barriers in poor glycemic control in our diabetic population.Patients and methodsThis cross-sectional study was conducted among 480 already diagnosed diabetes outpatients attended in our two hospitals. Glycaemic control was defined by levels of HbA1c. Socio-demographic data, lifest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
14
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 46 publications
4
14
0
4
Order By: Relevance
“…45 In the study conducted by Pokhrel, those patients who had a better understanding of diabetic complications and their management showed fair glycemic control. 46 In this study, decision-making was the strongest predictor of self-care behaviors (ß= 0.451). Self-care decision making in chronic illness seems warranted so that the complexities inherent in this process can be more fully understood.…”
Section: Discussionmentioning
confidence: 53%
“…45 In the study conducted by Pokhrel, those patients who had a better understanding of diabetic complications and their management showed fair glycemic control. 46 In this study, decision-making was the strongest predictor of self-care behaviors (ß= 0.451). Self-care decision making in chronic illness seems warranted so that the complexities inherent in this process can be more fully understood.…”
Section: Discussionmentioning
confidence: 53%
“…Other studies in Jordan, Kuwait, Bosnia, Nepal, Lebanon, Malaysia and Italy reported 23 to 43% of the prevalence of very good glycemic control, which was roughly the same as our study. Most studies assumed the diversity of glycemic control status to be due to the difference in sample size, duration of DM, and the degree of medication adherence [3,4,9,[16][17][18][19].…”
Section: Discussionmentioning
confidence: 99%
“…While better self-care leads to better glycemic control, 45 poor glycemic control is associated with poor adherence to self-care and becomes a barrier to performing self-care activities in patients with diabetes. 46 Although inconvenience was a commonly reported barrier to the performance of self-care behavior in the literature, 47 the present study suggests that patients' quality of life was maintained despite the increased frequency of self-care practices. Particularly, while no significant difference in ADDQOL was observed in the intervention arm, an alarmingly declining trend in this area for control patients was observed.…”
Section: Discussionmentioning
confidence: 51%